Addressing Socioeconomic Challenges Through Usage of Social Commerce in Business: A Social Network Theory and TAM Model Perspectives for Self-Help Groups - Dr. Mahasweta Saha; Subhadip Mitra (SocioEconomic Challenges)

(untitled)
Information and communication technologies like social commerce have empowered self-help groups and micro-entrepreneurs to bridge socioeconomic challenges. These technologies help them to reduce the complexity of the task, improve accessibility, eliminate intermediaries, and break conventional barriers. However, many of the self-help groups and their consumers may not be ready to adopt and use the social commerce applications for their business, as they are not easy to use and not perceived as useful. Hence, the aim of the study is to examine the impact of social commerce constructs on social support and social commerce information-seeking behavior leading to purchase intention of the self-help group consumers. A conceptual model is developed to examine the impact of perceived usefulness and perceived ease of use with the mediating role of social commerce information seeking based on the technology acceptance model and social network theory. A total of 566 responses were collected through a questionnaire in India during 2023–2024 and analyzed using Structural Equation Modeling (SEM). The results reveal that social commerce constructs have a significant impact on social support. Social support is found to have a significant impact on social commerce information seeking. The indirect effects of perceived ease of use and perceived usefulness on purchase intention — mediated by social commerce information seeking — are found to be significant, demonstrating the strong mediating role of social commerce information seeking. This study provides empirical evidence for all the direct and unique indirect relationships in the model. The mediating role of social commerce information seeking in the relationships between perceived usefulness and purchase intention, as well as between perceived ease of use and purchase intention, has not been adequately explored in previous studies. The findings will help marketers understand that the antecedents like social commerce constructs and social support help in developing social commerce information seeking for the consumers of the self-help groups. Further, social commerce information seeking may invoke consumers to develop purchase intention. Thus, self-help groups and micro-entrepreneurs may design relevant marketing strategies for gaining social support and try to develop the ‘easy to use’ and useful online technological interface for their consumers. Using technological applications like social commerce for business will help in the upliftment of the self-help groups and mitigate socioeconomic challenges.